Prevalence and predictors of cheating on antabuse: Is antabuse a cure or merely an obstacle? - Mustard, Sarah (American journal of criminal justice, 2006)
Descriptive tables and multivariate logistic regression models are used to explore the prevalence and predictors of consumption of alcohol (cheating) among a sample of clients being administered disulfiram (hereafter referred to as Antabuse) as part of a court-ordered alcohol treatment program for alcohol-related arrests. One in three respondents admitted to drinking alcohol while clients in a program where they were administered Antabuse as part of their court-ordered alcohol treatment. The results from the multivariate logistic regression models reveal that there are no significant differences in cheating by gender, race, age, and education. Additionally, those respondents who agreed that they would continue to drink upon completion of the alcohol treatment program were significantly more likely to have cheated than their counterparts without those intentions. Policy implications of these findings and ideas for future research are also discussed.